Preparation and characterization of conductive carbon black / polydimethysiloxane (PDMS) composite - Jaafar, Haslina; Abdul Aziz, Nur Haziqah; Mohd Sidek, Roslina; Hamidon, Mohd Nizar; Shafie, Suhaidi (Malaysian Solid State and Society, 2018)
This research comprises of preparation of carbon black nanoparticle and polymer for conductive composite and characterization of electrical properties for flexible electronic applications. Currently, conductive carbon nanotube-polymer composite is widely explored and recently applied in printed flexible and wearable sensors, RFID, optoelectronics circuit and solar cell. The carbon black-polymer conductive composite has good physical and electrical performance on flexible substrate and also low cost compared to other carbon materials. In this work, carbon black powder was mixed with Polydimethysiloxane (PDMS) and the curing agent to create the conductive carbon composite. Mixture of 5%CB, 7.5%CB, 10% CB and 12.5%CB of the composite were prepared and cured in an oven at 80°C. Electrical conductivity and mechanical properties were measured and observed. Sample with 12.5%CB has higher conductivity compared to the other samples. The mechanical characterization also shows that the sample with 12.5%CB has the lowest resistance changes as the force applied increased. This conductive carbon-polymer composite is very useful as a sensing material of flexible biosensors and electronics circuit for biomedical other potential applications.